A comprehensive review on fungal endophytes and its dynamics on Orchidaceae plants: current research, challenges, and future possibilities. Issue 1 (1st January 2019) - Sarsaiya, Surendra; Shi, Jingshan; Chen, Jishuang
ABSTRACT: In the development of medicinally important Orchidaceae, the extent of fungal endophytes specificity is not presently very clear. Limited study has been available on natural products formed and its role on plant growth, defence mechanism by endophytes, and to characterize the chief treasure of bioactive molecules. Therefore, this review article presents an evaluation of the endophytes associated with Orchidaceae for physiology, metabolism, and genomics which have prominently contributed to the resurgence of novel metabolite research increasing our considerate of multifaceted mechanisms regulatory appearance of biosynthetic gene groups encoding diverse metabolites. Additionally, we presented the comprehensive recent development of bio-strategies for the cultivation of endophytes from Orchidaceae and integration of bioengineered 'Genomics with metabolism' approaches with emphases collective omics as powerful approach to discover novel metabolite compounds. The Orchidaceae-fungal endophytes' biodynamics for sustainable development of bioproducts and its applications are supported in large-scale biosynthesis of industrially and pharmaceutical important biomolecules. Graphical abstract: uf0001